Carbon quantum dots supported ZnO sphere based photocatalyst for dye degradation application - Velumani, Arun; Sengodan, Prabhu; Arumugam, Priyadharsan; Rajendran, Ramesh; Santhanam, Sivakumar; Palanisamy, Maadeswaran (Current applied physics, 2020)
A Carbon quantum dots supported ZnO hollow Sphere (ZnO/C-dots) were synthesized through a solvothermal method using polyethylene glycol 400 (PEG 400) as a solvent. The phase and crystal structure of as-prepared ZnO/C-dots photocatalyst were characterized by powder X-ray diffraction (XRD). The surface morphology and size of the composite were analyzed using field emission scanning microscopy (FE-SEM). The optical properties of the as-prepared nanocomposites were examined using UV–visible (UV–Vis) spectrometer. The photocatalytic activity of pure ZnO and ZnO/C-dots nanocomposites were evaluated by the degradation of methylene blue (MB) under UV–Visible light irradiation. The ZnO/C-dots nanocomposites exhibited maximum photocatalytic MB dye degradation efficiency of 96% which is much higher that the pure ZnO (63%). The enhanced photocatalytic activity of ZnO/C-dots is due to the extended light absorption in the visible region and suppressed photoexcited electron-hole pair recombination rate. Moreover, the activity of photocatalyst after five cycles exhibits high stability, which is vital for the sustainable photocatalytic procedures. It is concluded that the prepared ZnO/C-dots composite have low cost, good stability and has a great potential application for Photocatalytic dye degradation. [Display omitted] •The applications of ZnO sphere based photocatalyst were addressed.•ZnO/C-dots were synthesized through a solvothermal method.•The morphology and phase structure are characterized by various techniques.•Extended light absorption in the visible region and suppressed photoexcited electron-hole pair recombination rate.•ZnO/C-dots nanocomposite is stable and exhibits excellent reusability.